Atributos químicos do solo, fisiologia, nutrição e produção de melancieira sob efeitos da salinidade hídrica, cobertura morta e adubação potássica - Bezerra, Francisco Thiago Coelho (2017)
The low and uneven precipitation in arid and semi-arid regions, often associated with water use restriction due to excess salts is a major limiting to agricultural development in these regions. Thus, the research was conducted in order to evaluate changes in chemical attributes Entisol, physiology, nutrition and production plants and quality of irrigated watermelon with saline water, soil cover and potassium doses in spring crops and summer. The treatments were organized in split-plot, with the main plot consisting of the electrical conductivity of irrigation water (0.3 dS m-1 and 3.0 dS m-1), and the subplots of the combinations of levels of soil cover (without and with) and doses of potassium (0, 40, 80 and 120 kg ha-1 of K2O), obeying the respective 2 x 2 x 4 scheme. A randomized complete block design was used. The chemical attributes Entisol were determined at 0-20 cm depth, based on fertility and salinity variables. The physiological evaluations consisted of determination of leaf chlorophyll indexes, chlorophyll a fluorescence and gas exchange. The evaluation of the nutritional status of the plants consisted of foliar levels of macronutrients, micronutrients, sodium and the nutritional balance index. At harvest were determined production components, productivity and fruit quality. Data were analyzed for the growing seasons, when jointly residual variances were homogeneous by Hartley Fmax test. The data were submitted to analysis of variance (ANOVA), Pearson correlation (ρ) and main components (PCA). It was also prepared Heatmap aiming to synthesize the information. The environmental conditions were more stressful spring plants, as evidenced by the lower quantum efficiency of photosystem II, higher initial and maximum fluorescence of chlorophyll a, chlorophyll b highest rate, higher nutritional imbalance and lower production. The use of irrigation Entisol cultivated with watermelon increased the electrical conductivity of the saturation extract and should be used sparingly in times of increased water demand as in the spring. The increase of salinity increased the nitrogen, manganese and sodium leaf contents and decreased iron leaf content, stomatal conductance, plant transpiration, fruit size and sweetness, but without affecting productivity. The use of mulch is not adequate in areas irrigated with water of 3.0 dS m-1 when the irrigation requirement is high, as in spring, when the sodium content increased. But, in general, the use of mulch is indicated in the cultivation of melancholia, since it increased the number of fruits and the yield per plant. Fertilization with potassium chloride can be used efficiently to raise soil exchangeable and soluble potassium contents. Since the application of potassium chloride is not recommended in Entisol with an average content of potassium, for the conditions in which the work was carried observed reduction in the number of fruits per plant in productivity and sweet taste (ratio of soluble solids and titratable acidity) of watermelon fruits.